Оценка погрешностей и области использования математической модели колебаний корпуса гусеничной машины при движении по пересеченной местности - Александров, Евгений Евгеньевич; Пидашов, В. В. (НТУ "ХПИ", 2007)
Lapses which originate at implementation of mathematical model of oscillations of the hull of the track vehicle are investigated. The comparative analysis of exact and approximated models is conducted. The estimation is given and possible areas of use of the indicated models are considered.
Keywords: гусеничные машины; погрешности колебания корпуса; система подрессоривания; плавность хода машины; натяжение гусеницы; нагруженность ходовой системы